Instagram Marketing Strategies for Culinary MSMEs: A Qualitative Study of Abdo's - Adi Muhamad Nazir; Inty Nahari; Fitria Fitria (Soegijapranata Catholic University, 2026)
This study analyzes the digital marketing strategy of Abdo's, a local culinary micro, small, and medium enterprise (MSME) in Surabaya, through Instagram. A descriptive qualitative case study was applied using Instagram observation, semi-structured interviews with the co-owner/social media administrator and a customer, and documentation of posts, stories, testimonials, and insights. The findings show that Abdo's relies on cinematic food reels, daily stories, persuasive captions, local hashtags, customer testimonials, direct messages, and limited food-vlogger collaboration. Cinematic food videos were perceived as the most effective content because they visualize product quality, texture, and consumption experience. Nevertheless, Instagram management still faces constraints related to inconsistent content scheduling, limited human resources, uneven visual quality, underused highlights, incomplete price information, and irregular promotions. The study recommends a weekly content calendar, consistent visual identity, complete product information, optimized reels, stories and highlights, stronger user-generated content, and regular insight evaluation. The findings imply that Instagram can function not only as a promotional showcase but also as a brand communication space that supports trust-building and purchase interest among culinary MSME customers.